Lost in the 20th Century. Concerning the Histories of Villages near Bełchatów Prior to the Mining of Brown Coal (An Outline of Research Topics Based on the Particular Example of the Village of Wola Grzymalina) - Czepas, Piotr (Studia Etnologiczne i Antropologiczne, 2020)
This article presents ethnographic research undertaken in the region of Bałchatów at the initiative of the Archaeological and Ethnographic Museum in Łódź. The primary focus of the research is upon villages that do not exist at present, having been liquidated during the construction of the brown coal opencast mine known as “Bełchatów”. Of special interest has been the village of Wola Grzymalina, nonexistant since the 1980s. The study’s objective has been to reconstruct the village’s spatial layout, including traces of the social and economic lives of its residents, and to track the liquidation process itself. Special attention has been paid to the building industry, small industry and crafts, and commercial contacts. The study has also located material remnants of the former village which survived thanks to relocation. The research at hand is presented against a backdrop of the archaeological and ethnographic works which had been completed prior to the building of the mine.